Topical Medication Adherence and Visual Field Progression in Open-angle Glaucoma: Analysis of a Large US Health Care System. Issue 12 (December 2021) - Shu, Yu-Hsiang; Wu, Jun; Luong, Tiffany; Mattox, Cynthia; Fang, Ervin N.; Lee, Brian L.; Jones, Jason P.; Campbell, Joanna; Shih, Vanessa; Zhao, Changgeng; Fong, Donald S.
Abstract : Précis: Modeling of visual field and pharmacy data (Kaiser Permanente, 2001 to 2014) from open-angle/pseudoexfoliation glaucoma patients in clinical practice indicated a significant inverse association between the level of medication adherence and rate of visual field progression. Purpose: The aim was to quantify the effect of nonadherence to topical hypotensive medication on glaucomatous visual field progression in clinical practice. Methods: Retrospective analysis of combined visual field and pharmacy data from Kaiser Permanente Southern California's HealthConnect electronic health record database. Patients with a diagnosis of primary open-angle glaucoma or pseudoexfoliation glaucoma (2001 to 2011) and ≥3 subsequent visual field tests of the same Swedish Interactive Threshold Algorithm type were followed up from first medication fill to final visual field test. Medication adherence (proportion of days covered) was estimated from pharmacy refill data. A conditional growth model was used to estimate the effect of adherence level in modifying the progression of mean deviation over time after adjusting for potential confounders, including age, sex, race/ethnicity, baseline glaucoma severity, and comorbidity. Results: In total, 6343 eligible patients were included in the study and followed for (mean) 5.8 years; average treatment adherence during follow-up was 73%. After controlling for confounders and the interaction between time and baseline disease severity, the model indicated that mean deviation progression was significantly ( P =0.006) reduced by 0.006 dB per year for each 10% (absolute) increase in adherence. Model estimates of time to glaucoma progression (mean deviation change −3 dB from baseline) were 8.3 and 9.3 years for patients with adherence levels of 20% and 80%, respectively. Conclusions: Improving patient adherence to topical glaucoma medication may result in slower deterioration in visual function over time.